Influência da privação do sono e do estresse emocional na dor miofascial em músculos mastigatórios de ratos - Alves, Bruno Wesley de Freitas (2021)
Masticatory myofascial pain is one of the most common causes of musculoskeletal pain in the orofacial region. Psychosocial factors, such as stress and sleep disorders, can negatively influence orofacial myofascial pain. The role of sleep disturbances in myofascial pain in masticatory muscles has not yet been investigated to date and nor the association between emotional stress and sleep disorders. Thus, the purpose of the present study was to investigate the influence of sleep deprivation and emotional stress on masticatory muscles nociceptive sensitivity in rats. For this, forty male Wistar rats were submitted to emotional stress model in Communication Box and paradoxical sleep deprivation in multiple platforms method. Animals were divided into four groups: control; emotional stress (ES); sleep deprivation (SD); and emotional stress associated with sleep deprivation (ESSD). Mechanical nociceptive tests, Openfield test and Y-maze test were performed to investigate the hyperalgesia in masseter and temporalis muscles, the locomotory and exploratory activities and the working memory, respectively. c-Fos expression was assessed in trigeminal ganglia (TG), spinal trigeminal nucleus caudalis (Sp5C), thalamus (THA) and periaqueductal gray (PAG). The presence of cytoplasmic vacuoles in adrenal glands were analyzed. The ES, SD and ESSD groups showed mechanical hyperalgesia in the masticatory muscles and the ESSD group showed a higher hyperalgesic response. There was an increase in c-Fos expression in TG, Sp5c and PAG in the ES, SD and ESSD groups. In THA, only the ES and ESSD groups showed an increase of c-Fos expression, but this did not occur in the SD group. In addition, there were an increase in exploratory and locomotor activities, a decrease in working memory and an increase in the concentration of cytoplasmic vacuoles in the adrenal glands in ES, SD and ESSD groups. In conclusion, emotional stress and sleep deprivation caused hyperalgesia in the masticatory muscles with involvement of the trigeminal nociceptive pathway through the expression of cFos in various regions, including descending pain modulatory brain area. The association of emotional stress with sleep deprivation exacerbated the pain sensitivity and provoked anxietylike behaviors and changes in adrenal glands, probably related to stress-induced neuroendocrine changes.